2019
DOI: 10.1289/ehp5260
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Toxicity Assessment of Piperonyl Butoxide Exposure Targeting Sonic Hedgehog Signaling and Forebrain and Face Morphogenesis in the Mouse: An in Vitro and in Vivo Study

Abstract: Background:Piperonyl butoxide (PBO) is a pesticide synergist used in residential, commercial, and agricultural settings. PBO was recently found to inhibit Sonic hedgehog (Shh) signaling, a key developmental regulatory pathway. Disruption of Shh signaling is linked to birth defects, including holoprosencephaly (HPE), a malformation of the forebrain and face thought to result from complex gene–environment interactions.Objectives:The impact of PBO on Shh signaling in vitro and forebrain and face development in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…The utility of animal models in this context is elegantly illustrated in studies of mice harboring a single allele mutation in the sonic hedgehog (Shh) gene, which is typically silent. Relative to wild-type controls, Shh mutant mice were found to exhibit enhanced sensitivity to the teratogenic effects of the pesticide synergist piperonyl butoxide [188]. Similarly, point mutations in RYR, which are silent under normal physiologic conditions, confer susceptibility to malignant hyperthermia (MH) triggered by exposure to halogenated anesthetics [74].…”
Section: Mechanisms By Which Pcbs Might Influence Asd Riskmentioning
confidence: 99%
“…The utility of animal models in this context is elegantly illustrated in studies of mice harboring a single allele mutation in the sonic hedgehog (Shh) gene, which is typically silent. Relative to wild-type controls, Shh mutant mice were found to exhibit enhanced sensitivity to the teratogenic effects of the pesticide synergist piperonyl butoxide [188]. Similarly, point mutations in RYR, which are silent under normal physiologic conditions, confer susceptibility to malignant hyperthermia (MH) triggered by exposure to halogenated anesthetics [74].…”
Section: Mechanisms By Which Pcbs Might Influence Asd Riskmentioning
confidence: 99%
“…Embryos were exposed from 6 to 24 hpf. This period of exposure was chosen to include the period of susceptibility for alcohol‐ and PBO‐induced HPE‐associated midfacial defects described in mice (Everson et al, 2019; Kietzman et al, 2014). At the end of the dosing period (24 hpf), the drug and embryo medium were removed and replaced with new embryo media.…”
Section: Methodsmentioning
confidence: 99%
“…It inhibits an insect’s cytochrome P450 detoxification enzymes, thereby augmenting the pesticidal activities of the active ingredient(s) ( e.g., pyrethroid pesticides). While PBO use is widespread, the potent developmental hazard of PBO was only recognized recently with the discovery that PBO can block Hh signaling (Everson et al, 2019; Horton et al, 2011; Wang et al, 2012).…”
mentioning
confidence: 99%
“…In mice, loss of both Shh alleles results in severe HPE, whereas heterozygous mice are indistinguishable from wild-type littermates. However, studies have shown that these 'silent' mutations dramatically exacerbate the teratogenicity of environmental chemicals, including ethanol and piperonyl butoxide (Everson et al, 2019;Kietzman et al, 2014). Similar experiments have shown additive or synergistic interactions between additional gene-environment pairs including Cdon and ethanol (Hong and Krauss, 2012), Gli2 and ethanol (Kietzman et al, 2014), and Gli2 and the synthetic smoothened antagonist vismodegib (Heyne et al, 2016).…”
Section: Introductionmentioning
confidence: 94%
“…Following the discovery of cyclopamine, numerous small molecules have been identified as pathway inhibitors acting through the same smoothenedtargeted mechanism (Pietrobono and Stecca, 2018;Rimkus et al, 2016). Such small molecules include diverse environmental chemicals, such as phytocannabinoids (Khaliullina et al, 2015) and a widely used pesticide synergist, piperonyl butoxide (Everson et al, 2019). Alcohol (ethanol), a known human teratogen, can also be added to this mix and has been suggested to act on multiple factors upstream of and within the Shh signaling cascade to disrupt development of the face and brain (Sulik, 2005).…”
Section: Introductionmentioning
confidence: 99%